Análisis espacio temporal del índice de vegetación de diferencia normalizado y su relación con variables climáticas en los ecosistemas naturales de la provincia de Loja - García Mendieta, Raúl Geovanny (2024)
Over the last decades, the natural ecosystems in the province of Loja have suffered several anthropogenic hazards. At the same time, as a result of climate change, the presence of extreme weather events and climate variability have caused an unknown pattern of behavior in the ecosystem dynamics. Therefore, the following objectives were set: to analyze the variation of NDVI as a function of temperature and precipitation in twelve ecosystems, and to define strategic guidelines to improve their adaptation to climate change. The methodology is based on the time series generation that identified seasonality patterns. To define the existence of a trend, and its upward or downward direction, the Mann-Kendall test was used, which consists of a p-value with a significance level of 95 % and a positive or negative Tau value. The Theil-Sen test was used to calculate the slope of the trend. For spatial dependence, a theoretical model was used to quantify the range and plateau of the semivariogram. For the adaptation of ecosystems to climate change, strategic guidelines were established. Mann-Kendall results with a p-value < 0.01 and a positive Tau indicate the presence of upward trends. On the other hand, the Theil-Sen slope in NDVI and temperature is higher in lowland deciduous forest of Jama Zapotillo, and in precipitation in montane evergreen shrubland of the southern Andes. The spatial dependence of the highest range between NDVI and temperature occurred in the Forest and semi-deciduous shrubland of the southern Valles with 7 592 meters, and in precipitation in Forest and semi-deciduous shrubland of the southern Valles the range reached 9 779 meters. The strategic guidelines focused on improving climate models at the local scale, ecosystem restoration and building capacity. The research concludes as follows: 1) Half of the seasonality followed a chronological order of temperature- precipitation-NDVI. 2) In the trends, the greatest temperature increase occurred in the forests and shrublands of Jama Zapotillo and Páramo Grassland, jeopardizing their normal functioning and ecosystem services. 3) The strategic guidelines represent an important framework in the management, implementation and monitoring of activities that allow the populations and ecosystems under study to reduce their vulnerability to climate change.